Question about Casio FX82MS Scientific Calculator

Ad

then x = 3y-12, then 4(3y-12) +6y=-12, then (12y-48)+6y=-12, then 12y-48+6y=-12, then 18y=36, then y=2. x=3y-12, x=3(2)-12, x=6-12, x=-6.

Mar 05, 2015 | Office Equipment & Supplies

Let the two numbers be X and Y:

X + 3Y = 5

2X + Y = 8

Rewrite the second equation to Y = 8 - 2X and substitute in first equation:

X + 3(8-2X) = 5

X + 24 - 6X = 5

-5X + 24 = 5

-5X = 5 - 24

-5X = -19

X = 19/5 =**3.8**

Y = 8 - 2(3.8) = 8 - 7.6 =**0.4**

Check: 3.8 + 3(0.4) = 3.8 + 1.2 = 5

2(3.8) + .4 = 7.6 + 0.4 = 8

X + 3Y = 5

2X + Y = 8

Rewrite the second equation to Y = 8 - 2X and substitute in first equation:

X + 3(8-2X) = 5

X + 24 - 6X = 5

-5X + 24 = 5

-5X = 5 - 24

-5X = -19

X = 19/5 =

Y = 8 - 2(3.8) = 8 - 7.6 =

2(3.8) + .4 = 7.6 + 0.4 = 8

Nov 14, 2013 | Computers & Internet

You have to put the equations into matrix form first. To do this, each variable has one column in the first matrix and you fill in the co-efficients for the variables. The second matrix has one column and contains all the numbers.

{ 2 -1 1 -1} = Matrix A

{ 1 3 -2 0}

{ 3 -2 0 4}

{-1 -3 -3 -1}

{-1} = Matrix B

{-5}

{ 1}

{-6}

{x=-2} = A*(B^-1)

{y=-.2}

{z=3}

{w=1/6}

I used excel for all my calculation and a helpful tutorial can be found here. I hope this helps and have a nice day!

{ 2 -1 1 -1} = Matrix A

{ 1 3 -2 0}

{ 3 -2 0 4}

{-1 -3 -3 -1}

{-1} = Matrix B

{-5}

{ 1}

{-6}

{x=-2} = A*(B^-1)

{y=-.2}

{z=3}

{w=1/6}

I used excel for all my calculation and a helpful tutorial can be found here. I hope this helps and have a nice day!

May 05, 2011 | Computers & Internet

Type solve(exp1 and exp2 and exp3, {x,y,z})

See cap images

See cap images

Dec 15, 2010 | Texas Instruments TI-89 Calculator

Your missing some operators in your equations.

Aug 07, 2010 | Matrix 226R (VPR226R) PC Desktop

You can solve it with following method.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

Go to your matrix button and enter a "3x4" matrix.

Then enter it as follows:

-3 4 5 7

4 3 2 9

-5 5 3 -10

Then exit out and go to "2nd->matrix->math->rref(". Then press enter.

Your screen should look like this:

rref(

Then go to matrix and select your 3x4 matrix, press enter and close it with a parathesis. Your screen should look like this:

rref([A])

Press enter and the screen should say this:

1 0 0 2

0 1 0 -3

0 0 1 5

So,

x=3

y=-3

z=5

Hope this cleared up the confusion!

SJ_Sharks

Then enter it as follows:

-3 4 5 7

4 3 2 9

-5 5 3 -10

Then exit out and go to "2nd->matrix->math->rref(". Then press enter.

Your screen should look like this:

rref(

Then go to matrix and select your 3x4 matrix, press enter and close it with a parathesis. Your screen should look like this:

rref([A])

Press enter and the screen should say this:

1 0 0 2

0 1 0 -3

0 0 1 5

So,

x=3

y=-3

z=5

Hope this cleared up the confusion!

SJ_Sharks

Mar 03, 2009 | Texas Instruments TI-84 Plus Calculator

Consider the following system of **3 equations in 3 unknowns**:

*x + y = *2

**2***x + *3*y + z = *4

*x + *2*y + *2*z = *6Our goal is to transform this system into an equivalent system from which it is easy to find the solutions. We now do this step by step.
* x + y = *2

* y + z = *0

* y + *2*z = *4
*z = *4, *y = *-4, and *x =* 2*-*(*-4*)* = *6Equivalently, we say that the unique solution to this system is **(***x, y, z*) = (6, -4, 4).

- Subtract 2*(Row1) from Row2 and place the result in the second row; subtract Row1 from Row2 and place in the third row. Leave Row1 as is.

- Subtract Row2 from Row3, and place the result in row3. Leave Row1 and Row2 as they are.

Sep 17, 2008 | Belkin (F5D7230-4) Router (587009)

(13)3/8-(6)15/16

Jun 17, 2008 | Texas Instruments TI-84 Plus Silver...

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

16 people viewed this question

Usually answered in minutes!

×